Bank Specific and Macroeconomic Determinants of Commercial Bank Performance in Bangladesh - Bony, Shakila Zerin (ABC Journal of Advanced Research, 2021)
The main purpose of this study is to examine the impacts of bank-specific and macroeconomic factors on the commercial bank performance measures (ROA, NIM, and ROE in this case) in Bangladesh. The study identifies bank-specific characteristics and macroeconomic determinants of performance in Bangladesh’s banking sector over the years 2009 to 2018. The study uses relevant data from a sample of 10 commercial banks in Bangladesh. The determinants are identified by using correlation and regression analysis. This finding serves as an indicator that the bank-specific and macroeconomic variables selected for this study provide a better description of ROA rather than net interest margin (NIM) and ROE. Among all the bank-specific determinants board size, audit committee meetings, and foreign ownership have a positive relationship with the bank’s performance. Specifically, inflation and GDP are observed to have a positive relationship with bank performance. The findings of this research can be of great help to a wide range of entities such as academicians, bankers, the government, students, and investors. This study can be helpful to bank management by providing valuable information thus assisting in the construction of efficient management policy decisions in order to ensure higher profits.